Aetiology of urticaria in children - S. N. Buinova; V. M. Shinkareva (Acta Biomedica Scientifica, 2017)
Urticaria is a frequent disease in childhood, which almost every child had. Usually, the presence of distinct urticaria does not present difficulties in nosological diagnosis, but many factors in account for its development cause challenge for doctors in choosing tactics for therapy. Traditionally the triggers of urticaria in children are food allergens and drugs, and that is why pediatricians unreasonably eliminate many foods from the baby's nutrition for a long time. We analyzed the causes of acute and chronic urticaria in children hospitalized in the department of pediatrics over the ten-year period. In acute urticaria, in most cases, triggers were food (46.7 % children) and drugs (22.5 % children), in children with chronic urticaria, food was the cause of rashes only in 20 % of cases, and the infectious etiology of the disease was confirmed in 8 children. In almost a half of children with chronic urticaria the cause of the rash was not established. Based on the research, recommendations for the examination of patients with this pathology are suggested. Except for testing for food allergens and drugs, the diagnostic protocol of a patient with chronic urticaria should include the laboratory tests for infectious agents, as well as conducting fibrogastroduodenoscopy with biopsy of the gastric mucosa according to indications.